Effect of Sperm Extender and Dilution Ratio on The Sperm Motility, Fertility and Hatchability of Depik fish Rasbora Tawarensis (Pisces: Cyprinidae) Eggs - Muchlisin, Zainal Abidin; Aldila, Dhea Febby; Sarah, Putri Inten; Eriani, Kartini; Hasri, Iwan; Fadli, Nur; Muhammadar, Abdullah Abbas; Siti-Azizah, Mohd Nor; Kocabas, Filiz Kutluyer (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
The artificial breeding method for depik fish Rasbora tawarensis was not available, and the extenders and its dilution ratio are the crucial factors in artificial breeding of fishes. Herein, we tested several common sperm extenders and its dilution ratio  in the artificial breeding for depik fish. Two  series of experiments were performed to find the best extender and its dilution ratio. In the first experiment, five types of extenders, namely: Ringer’s solution, physiological solution, coconut water, sugarcane water, and roomie water. The second experiment studied four dilution levels of sperm and extender (v/v), namely: 1: 20, 1: 30, 1: 40, and 1: 50. Every treatment was conducted in four replicates and experiments were conducted in series so that the best results in the first experiment were used in the second.  The first experiment showed that Ringer’s is the best extender for depik sperm, and the second experiment revealed that Ringer’s at dilution ratio 1: 40 gave higher sperm motility, fertilization and hatching rates. Hence,  the best formula for the dilution solution of depik sperm is Ringer’s at the dilution ratio of 1: 40, sperm: extender (v/v).